Penentuan Penerima Bantuan Sosial Dana Desa Dengan Sistem Pendukung Keputusan Menggunakan Simple Additive Weighting Method - Muhamad Awiet Wiedanto Prasetyo; Devi Yunita Saputri; Afilda Trisetya Riziana (Jurnal Komputer Terapan, 2022)
The government has prepared social assistance for those affected by Covid-19, such as subsidized electricity tariffs for 450VA and 900VA, pre-employment card program, presidential assistance for productive micro-enterprises, subsidized assistance for workers' wages below Rp. 5,000,000., - as a BPJSTK participant, Jabodetabek basic food assistance, cash assistance outside Jabodetabek, Non PKH basic food card program assistance, distribution of cooperative loans through the KUMKM Revolving Fund Management Agency, as well as direct cash assistance from village funds. The main requirements are that the head of the neighborhood association and community unit has registered, lost their livelihood in the midst of the Covid-19 pandemic and is not registered as a recipient of other social assistance from the central government. However, in the field, it does not meet the expectations of the community, because it is considered not right on target. There needs to be a re-evaluation of the assistance program so that it is more targeted because it is not in accordance with the previous government's planning. by utilizing the Simple Additive Weighting Method, it can make it easier for the village government to determine the recipients of village fund social assistance. The results of existing calculations can be implemented on the previous platform (Web Based).